INVESTMENT RISKS IN THE ASSESSMENT OF THE LEVEL OF ECONOMIC DEVELOPMENT OF THE REGION - Topsakhalova, Fatimat; Urusova, Avgustina (Revista Inclusiones, 2020)
The relevance of the problem under investigation is defined by the rationale for the causes of the negative (and positive) impact of uncertainty and risk on the agrarian production of the region. The topicality of the paper is also determined by the problems of developing such methods for evaluating investment attractiveness, which allow to avoid a significant loss of information for the investor. The article aims to study the basic concepts and stages of the multicriteria process and the dynamic processes of the agricultural sphere. The main approach to the study of this problem is the use of sign, weighted sign and functional sign graphs, classical and multicriteria optimization of the construction of an economic and mathematical model for determining investment risk in the system for assessing the level of economic development of the region. The optimization is carried out under multicriteria conditions. The results of the research show the level of economic development of the region with the focus on the risk and uncertainty factors in the conditions of multicriteria approaches and the usage of sign graphs. At the same time, the analysis of various mathematical models applied to the study of investment risk dynamics has shown that it is advisable to use sign, weighted sign and functional sign graphs. The materials of the article can be used in the system of assessing the level of economic development of the region.